Sequence analysis of pothos latent virus genomic RNA - Rubino, Luisa; Russo, Marcello; Martelli, Giovanni P. (Journal of General Virology, 1995)
The complete genomic sequence of pothos latent virus (PoLV) has been determined. The genome organization is very similar to that of tombusviruses. The genome is 4415 nucleotides long and contains five ORFs. The 5′ ORF (ORF 1) encodes a protein with a predicted molecular mass of 25 kDa and readthrough of its amber stop codon results in an 84 kDa protein (ORF 2). ORF 3 encodes the 40 kDa capsid protein. Two nested ORFs (ORFs 4 and 5) in different reading frames encode 27 and 14 kDa proteins, respectively. Amino acid sequence alignments revealed significant similarities between the readthrough portion of ORF 2 and the coat protein (ORF 3) of PoLV and the corresponding proteins of several tombusviruses. Conversely, the predicted products of ORFs 1, 4 and 5 showed only limited similarity to the equivalent tombusvirus proteins. These results support the conclusion that PoLV is a new but atypical member of the family Tombusviridae.